I – “miesjcova“, You – “przyjiezny”: Drawing the Boundary of Identity in Šalčininkai District - Vyšniauskas, Vidmantas (Sociologija. Mintis ir veiksmas, 2021)
In this article, I seek to investigate how people living in the Šalčininkai district perceive the cultural boundary between locals and newcomers. Based on biographical interviews collected during the ethnographic field research, I argue that historical circumstances and frequent changes in state affiliation have influenced the drawing of the cultural boundary between locals and newcomers. In the article, I present how this division is understood by people of different generations living in the Šalčininkai district. The cultural boundary between locals and newcomers is very important to the oldest generation (born before World War II). People who grew up during Soviet times understand this boundary and its significance, but pay less attention to it. The youngest generation (people born around 1990) perceive this cultural boundary as a useless remnant of the past and want to distance themselves from it.